Tinjauan Yuridis terhadap Kompetensi Hakim Praperadilan dalam Membatalkan Status Tersangka Tindak Pidana Korupsi - Eko Nurisman; Lisbet Purba (Fakultas Hukum, Universitas Internasional Batam, 2018)
The purpose of this study was to analyze the juridical basis of the competence of the Pre Trial judge in cancelling suspect status and the legal basis in cancelling suspect status. Especially in this study case of the court case Number 97/Pid.Prap/2017/PN.Jkt.sel, pretrial filed by Setya Novanto. This study is reviewed from the relevant legislation, Regulation Number 8/1981 about Criminal Procedure Code (KUHAP). In this research, the metedology that used is law juridical normative research. The data was used by secondary data obtained from literature studies (library research). And then, after data was collected completely then it will be processed and analyzed, the analysis was used qualitative method, it means by using collecting data on the aspects studied. Further, the conclusion is related to this research, then described descriptively. Based on this research, the result obtained by the researcher from 2 (two) formulation of the problem, concerning of the Competence of Judge in Canceling Suspect Status of Setya Novanto and Judge Consideration Base in Canceling Suspect Status of Setya Novanto based on Decision No.97/Pid.Prap/2017/PN.Jkt.Sel., that the judge does not have the authority or competence to cancel the status of person’s suspect because it is not regulated in the law and also contradictory to Article 77 KUHAP. The judge in pretrial Cepi Iskandar by giving the decision has exceeded his duties and authority that had been regulated in KUHAP.